Periwinkle shell as mixing ingredient in concrete: A review - Ruslan, H. N.; Khairunisa, Muthusamy; Sharifah Maszura, Syed Mohsin; Kirgiz, M. S. (Penerbit UMP, 2021)
Growing population which also pushes for rising demand for seafood results in a generation of seashells which are thrown as environmental pollution waste after the edible meat is consumed. Meanwhile, the utilisation of natural resources as mixing ingredients for the production of concrete materials continues to increase over the year. The use of periwinkle shells as mixing ingredients in concrete materials can lower the dependency on natural aggregate supply. This paper discusses the properties of periwinkle shell and method of treatment prior to their usage as a cement and coarse aggregate as well as the mechanical properties of concrete produced using this seashell waste. Overall, the replacement of periwinkle shell as cement and coarse aggregate must be integrated in a specified percentage to enhance the performance of the concrete. For cement replacement, 5% of replacement gives the highest strength, meanwhile 10% of replacement as coarse aggregate can meet the desired strength. The increase in the use of periwinkle shell quantity as cement or coarse aggregate replacement reduces concrete workaibility. The integration of periwinkle shell influences the compresssive strength of concrete. Accomplishment in replacing periwinkle shell as cement and coarse aggregate would reduce pollutiion due to shell dumping and save natural resources. However, further investigation in terms of durability properties is recommended.